The nature and significance of the Hindu Divine Mother in embodied thealogical perspective. (October 2022) - Burley, Mikel
Abstract: The Hindu Divine Mother is revered by millions of religious practitioners in India and elsewhere, yet this goddess rarely receives attention in Western philosophy of religion. Focusing especially (though not exclusively) on her form as Kālī, this article utilizes sources from Hindu goddess traditions to explicate her contrasting characteristics, which include benign maternality and martial aggression. By adapting an embodied theological (or thealogical) approach derived from feminist discourse, the intelligibility of worshipping such a goddess is expounded; connections are delineated between the conceptualizing of divinity as radically ambivalent or multivalent and the lived experience of inhabiting an often hostile world.